2016
DOI: 10.1371/journal.pone.0162745
|View full text |Cite
|
Sign up to set email alerts
|

A Different Perspective on Evaluating the Malignancy Rate of the Non-Diagnostic Category of the Bethesda System for Reporting Thyroid Cytopathology: A Single Institute Experience and Review of the Literature

Abstract: ObjectiveTo determine the malignancy rate in the non-diagnostic (ND) category of the Bethesda System for Reporting Thyroid Cytopathology (BSRTC) based on a different approach in relation to histopathology diagnoses.Study DesignAll ND fine needle aspirations (FNAs) that were performed under ultrasound guidance by an interventional radiologist with rapid on-site evaluation were included in the study. Slides were reevaluated to identify the cause of inadequacy as “qualitative” or “quantitative.” The malignancy ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
7
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 25 publications
3
7
1
1
Order By: Relevance
“…As a matter of fact, regardless of the somewhat high rate of AUS/FLUS, the AUS/FLUS:malignant ratio in the current study did not exceed 3 (417/149 = 2.8), thereby supporting the quality of our practice . Our reported ROMs for the ND and AUS/FLUS categories were greater than those proposed by the updated TBSRTC, but still comparable to previously reported experiences regarding what can be affected directly and biased by the selection of clinically suspicious nodules for surgery and a higher incidence of malignancies in a cancer center environment . The ROMs for the malignant category reported herein (92.6% in the non‐ROSE group and 93.8% in the ROSE group) were lower than those estimated by the first edition of TBSRTC (range, 97%‐99%) .…”
Section: Discussionsupporting
confidence: 73%
“…As a matter of fact, regardless of the somewhat high rate of AUS/FLUS, the AUS/FLUS:malignant ratio in the current study did not exceed 3 (417/149 = 2.8), thereby supporting the quality of our practice . Our reported ROMs for the ND and AUS/FLUS categories were greater than those proposed by the updated TBSRTC, but still comparable to previously reported experiences regarding what can be affected directly and biased by the selection of clinically suspicious nodules for surgery and a higher incidence of malignancies in a cancer center environment . The ROMs for the malignant category reported herein (92.6% in the non‐ROSE group and 93.8% in the ROSE group) were lower than those estimated by the first edition of TBSRTC (range, 97%‐99%) .…”
Section: Discussionsupporting
confidence: 73%
“…The rate of non-diagnostic specimens was found to be 22.6% in our study. This is higher than what has been reported in the literature [ 6 15 , 19 , 20 , 22 ]. Reasons for this difference might include that the daily number of patients per physician was higher in our hospital, physicians who perform aspirations in our hospital were allowed an average of four minutes for each patient and the aspirations were performed using a single needle.…”
Section: Discussioncontrasting
confidence: 62%
“…In our study, the total number of benign and non-diagnostic categories accounted for 90.9% of cases. In the literature the rate has been reported to range from 59% to 84% [ 6 20 , 23 ]. Bongiovanni et al found in their meta-analysis that this rate was about 72% [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nondiagnostic (ND) thyroid FNA result remains a major constraint in arriving at a definitive diagnosis and is the most common cause of false negative reports [4]. It is difficult to assess the risk of malignancy for the ND category because only a small subset of ND nodules undergoes resection.…”
Section: Discussionmentioning
confidence: 99%
“…Gunes et al stated that the clinical expertise of the person performing the FNA, ultrasound guidance, and rapid on-site evaluation for specimen adequacy were not uniform between studies which contributes to the wide range of malignancy rate. All these determinants make the comparison between studies cumbersome and should be taken into consideration while labelling a specimen as nondiagnostic and assessing the risk of malignancy [4]. Some of the studies stated that the operator experience and the number of passes made during FNA correlate with the nondiagnostic result [7,8].…”
Section: Discussionmentioning
confidence: 99%